Pressure-induced expression changes in segmental flow regions of the human trabecular meshwork. (May 2017) - Vranka, Janice A.; Acott, Ted S.
Abstract: Elevated intraocular pressure (IOP) is thought to create distortion or stretching of the juxtacanalicular and Schlemm's canal cells and their extracellular matrix (ECM) leading to a cascade of events that restore IOP to normal levels, a process termed IOP homeostasis. The ECM of the trabecular meshwork (TM) is intricately involved in the regulation of outflow resistance and IOP homeostasis, as matrix metalloproteinase (MMP)-initiated ECM turnover in the TM is necessary to maintain outflow facility. Previous studies have shown ECM gene expression and mRNA splice form differences in TM cells in response to sustained stretch, implicating their involvement in the dynamic process of IOP homeostasis. The observation that outflow is segmental around the circumference of the eye adds another layer of complexity to understanding the molecular events necessary to maintaining proper outflow facility. The aim of this work was to identify molecular expression differences between segmental flow regions of the TM from anterior segments perfused at either physiological or elevated pressure. Human anterior segments were perfused in an ex vivo model system, TM tissues were extracted and quantitative PCR arrays were performed. Comparisons were made between high flow and low flow regions of the TM from anterior segments perfused either at normal (8.8 mmHg) or at elevated (17.6 mmHg) perfusion pressure for 48 h. The results are presented here as independent sets: 1) fold change gene expression between segmental flow regions at a single perfusion pressure, and 2) fold change gene expression in response to elevated perfusion pressure in a single flow region. Multiple genes from the following functional families were found to be differentially expressed in segmental regions and in response to elevated pressure: collagens, ECM glycoproteins including matricellular proteins, ECM receptors such as integrins and adhesion molecules and ECM regulators, such as matrix metalloproteinases. In general, under normal perfusion pressure, more ECM genes were enriched in the high flow regions than in the low flow regions of the TM, whereas more ECM genes were found to be enriched in low flow regions of the TM in response to elevated perfusion pressure. Thus it appears that a limited subset of ECM genes is differentially regulated in both high and low flow regions and in response to elevated pressure. Some of these same ECM genes have previously been shown to be involved in the pressure response of stretched TM cells supporting their central role in IOP homeostasis. In general, different ECM gene family members are called upon to produce the response to elevated pressure in different segmental regions of the TM. Highlights: ECM genes are differentially expressed in high flow versus low flow regions. A set of ECM genes is differentially expressed in response to elevated pressure. ECM genes in segmental flow regions have differential responses to pressure. ECM turnover in response to elevated pressure is critical to IOP homeostasis. ECM remodeling in response to elevated pressure is part of IOP homeostasis.